PENGARUH PENGGUNAAN METODE PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Martinawati, Martinawati; kamid, Kamid; Asyhar, Rayandra (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2013)
This study aims to determine the effect of the method of learning and cognitive style on learning outcomes of junior high school math students. Research conducted at SMP Negeri 6 Tungkal Ulu, in classVII, the second semester in the Academic Year 2012/2013. The research design uses 3x2 factorial design. One treatment/factor with three levels (X1, X2 and X3) and the moderator variable that has two levels (Y1 and Y2). Research instrument stome asure the independent variable is the design of learning motede partisifatip on class treatment and conventional learning methods in the design of the control class, while the moderator variables using the Group embedded figures test(GEFT). Processing data using ANOVA and Tukey's test double row.Research results sho wthat: first, there is the effect of using the learning method possible to junior high students 'mathematics learning out comes, secondly, there is the influence of cognitive style on junior high school students' mathematics learning out comes; Third, there was nosignifi cant interaction between the use of methods of learning and cognitive style on learning out comes of mathematics junior high school students; fourth, mathematics learning out comes of students whouse the group discussion method is better than the mathematics learning out comes using conventional methods; fifth, mathematics learning out comes of students whouse traditional methods buzz group discussion better than metematika learning out comes using conventional methods. sixth, learning out comes using group discussions as well as the mathematics learning out comes using buzz group discussions; seventh, mathematics learning out comes of students who have the cognitive style of field Independent better learning out comes of students who have cognitive styles Dependent field. In connection with the results of the study, it is suggested that the use of participatory learning methods used asan alternative learning method in order toimprove student learning out comes in particular subject are as of mathematics, and can al sobe used in other fields of study. Keyword : Method of learning and cognitive styles, learning out comes mathematics